The Relevance Of Hindu God Concepts And Arguments Proving The Existence Of God Perspective Gottfried Wilhelm Leibniz - Krisna S. Yogiswari (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
Gottfried Wilhelm Leibniz is a German philosopher who provides a comprehensive argument about the existence of God. Although Leibniz has made a mistake in thinking about God, the evidence of God’s presence offered by him gives us an example and a strength to deepen our faith: Leibniz’s courage is to increase his confidence and his power to maintain God's existence. The arguments presented by Leibniz are very relevant to the concept of God in Hinduism. It also seems that with evidence of harmony that had already been built before, Leibniz fell into the trap of atheism implicitly because it denied the existence of a personal God and only relied on internal law. Regarding the harmony that had already been built before, Leibniz explained that civil laws were working in monade. Monade are predetermined natures, which result in having one characteristic that governs everything. But the best is that not only for the whole in general but also for individuals, especially individuals who have a love for God.